2018
DOI: 10.1186/s12885-018-4469-4
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT incidental detection of second tumor in patients investigated for pancreatic neoplasms

Abstract: BackgroundPositron Emission Tomography/computed tomography (PET/CT) is an imaging technique which has a role in the detection and staging malignancies (both in first diagnosis and follow-up). The finding of an unexpected region of FDG (Fluorodeoxyglucose) uptake can occur when performing whole-body FDG-PET, raising the possibility of a second primary tumor. The aim of this study was to evaluate our experience of second primary cancer incidentally discovered during PET/CT examination performed for pancreatic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…To detect SPMs or visceral KS in patients with KS, EGD/CS is a more useful approach than positron-emission tomography (PET)/CT. PET/CT has been well-reported to detect SPMs in various body sites of patients with primary cancer [42][43][44][45]. However, we recommend EGD/CS for these patients for the following reasons: First, PET/CT may overlook SPMs because it potentially overlooks small-sized upper gastrointestinal cancer and colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To detect SPMs or visceral KS in patients with KS, EGD/CS is a more useful approach than positron-emission tomography (PET)/CT. PET/CT has been well-reported to detect SPMs in various body sites of patients with primary cancer [42][43][44][45]. However, we recommend EGD/CS for these patients for the following reasons: First, PET/CT may overlook SPMs because it potentially overlooks small-sized upper gastrointestinal cancer and colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 The rate of CaP detected in FDG PET prostate incidentalomas is variable in prior reports. 1 Han et al evaluated 87% of patients with a prostate incidentaloma and found that 5.4% represented CaP. 12 Bertagna et al evaluated 22.5% of patients with PSA and biopsy and found CaP in 55.5% of evaluated cases, or 12.5% of the overall cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Incidentalomas are commonly observed, occurring in approximately 10-14% of FDG PET scans. 1,2 Some of these incidentalomas are located within the prostate in the absence of known CaP. The rate of prostate incidentaloma on FDG PET has been reported in two series as 0.086% 9 and 1.4%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations